THE ROLE OF BLOCKCHAIN TECHNOLOGY IN ENHANCING FINANCIAL TRANSPARENCY - Bakoeva Gulbakhor (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article explores how blockchain technology contributes to improving financial transparency within both public and private sectors. It examines blockchain’s fundamental characteristics—decentralization, immutability, and traceability—and their implications for reducing corruption, increasing accountability, and ensuring data integrity. The study highlights real-world applications of blockchain in banking, auditing, and government finance, as well as its challenges and future potential. Drawing upon empirical studies and global initiatives, the article demonstrates that blockchain has become a cornerstone technology for transparent and secure financial ecosystems.